The Effectiveness Of Eye Movement Desensitization And Reprocessing (EMDR) On Iraqi Child War Victims With Posttraumatic Stress Disorder (PTSD) In Baghdad - Wadaa, Najlaa N (2011)

(untitled)
Posttraumatic stress disorder (PTSD) is an anxiety disorder following a serious traumatic event that causes three clusters of symptoms: re-experiencing, avoidance and hyperarosal for survivors. Many Iraqi children have developed traumatic symptoms following the exposure to the current war. Their lives are filled with pain and distress; hence, there is an acute need to explore an effective treatment for the traumatized children. One such treatment is Eye Movement Desensitization and Reprocessing (EMDR), which is approved and recommended by professionals as an empirically supported method of treatment for PTSD.